Growth of a Modern Union Local: A People's History of SEIU Local 880 - Kelleher, Keith (Just Labour: A Canadian Journal of Work and Society, 2008)
This article examines the growth of one of the fastest-growing union locals in North America, the Services Employees International Union Local 880 in Chicago. As union membership has declined nationally, Local 880 has achieved exponential growth over the last twenty five years by being among the first to organize extremely low wage home based child care and home care workers. The article highlights the tenets of the local's organizing philosophy, including community organizing and political activism, as well as other strategies and tactics 880 has utilized in growing its membership to more than 65,000 members. Along the way, it has secured notable victories on behalf of its members, including winning the largest organizing campaign of home childcare workers in U.S. history.